Effectiveness of dignity therapy on advanced cancer patients: A meta-analysis (尊严疗法对晚期癌症患者干预效果的Meta分析) - ZHANG Saina (张赛娜); FAN Na (范娜); ZHANG Qin (张琴) (中西医结合护理)
Objective To systematically evaluate the impact of dignity therapy on dignity, hope and quality of life of patients with advanced cancer. Methods Studies published in databases such as PubMed, Embase, Web of Science, Cochrane Library, EBSCO, Scopus, CNKI, WanFang Data, VIP, CBM were searched by computer from the establishment to April 2023. Researchers had screened the literature, extracted data and quality assessment according to the inclusion and exclusion criteria. Meta analysis of the included references was performed using RevMan 5. 4 software. Results A total of 1183 patients were included in 12 studies. The results of meta-analysis showed that dignity therapy could improve the dignity, raise the hope(P＜0. 01). However, the effect of quality of life was unclear(P=1. 00). Conclusion The existing evidence shows that dignity therapy can improve the dignity and raise the hope of advanced cancer patients, but it has not been found to improve the quality of life, which needs to high-quality, large sample studies with a long intervention period to explore the impact of dignity therapy with advanced cancer patients. (目的 系统评价尊严疗法对晚期癌症患者尊严状况、希望水平和生活质量的干预效果。方法 计算机检索PubMed、Embase、Web of Science、Cochrane Library、EBSCO、Scopus、中国知网(CNKI)、万方(Wanfang Data)、维普(VIP)和中国生物医学文献数据库(CBM), 检索时限为建库至2023年4月。根据文献的纳入及排除标准, 筛选文献并进行资料提取和质量评价, 采用RevMan5. 4软件进行Meta分析。结果 共纳入12篇文献, 1183例患者。Meta分析结果显示, 尊严疗法可有效改善晚期癌症患者的尊严状况和提高希望水平(P＜0. 01), 但对生活质量影响不大(P=1. 00)。结论 现有证据表明, 尊严疗法能有效改善晚期癌症患者的尊严状况, 提高希望水平, 尚未能发现提高患者的生活质量, 还需要高质量、大样本、干预周期较长的研究进一步探讨尊严疗法对患者的影响。)